Anchoring resveratrol on surface of electrospun star-shaped PCL-COOH/PLLA fibers. Issue 11 (23rd July 2020) - Zhang, Xue; Wang, Lei; Han, Libin; Wang, Yanhe; Dai, Boya; Song, Xiaofeng
Abstract: Skin defect that is not able to regenerate by itself is a challenging and growing problem. Development of a novel bionic scaffold that promotes healing process has received an increasing interest in recent years. In this study, a star-shaped PCL-COOH/PLLA fiber mat anchoring resveratrol was developed. FTIR and 1 HNMR confirmed that resveratrol was covalently grafted onto the fiber surface. And the fibrous morphology was kept well. The Xc of fiber mat slightly reduced after anchoring resveratrol, but it still exhibited good thermal stability. Its tensile strength and elongation at break were about 1.0 MPa and 10.3%, respectively. The wettability of fiber mat anchoring resveratrol was significantly improved compared to PLLA. And it was no cytotoxicity, and facilitated NHDF cell viability. Then the prepared fiber mat is a prospective material for skin engineering applications. Graphical Abstract: A star-shaped PCL-COOH/PLLA fiber mat anchoring resveratrol has been developed as the candidate for skin tissue engineering. It exhibits good thermal and mechanics stability. The nontoxic fiber mat provides a good site for NHDF cell viability.